Does the EU LEADER instrument support endogenous development and new modes of governance in Romania?: Experiences from elaborating an MCDA based regional development concept - Doris Marquardt; Stefan Wegener; Judith Möllers (International Journal of Rural Management, 2010)
The well-known EU LEADER programme aims at using the endogenous potential of rural regions and at improving local governance. Especially since the current funding period doubts are rising about whether the programme actually delivers what it promises. Indeed, translating the LEADER approach is a challenge, not only for new EU member states. This paper looks at the case of post-socialist Romania where the programme is implemented for the first time. Our research questions are (a) in how far an endogenous approach can be practically implemented by local initiatives and (b) how the LEADER implementation contributes to the adoption of new modes of governance. We draw on a case study in which a potential Romanian Local Action Group has been externally supported in elaborating a Regional Development Concept. We observed the participatory decision-making process among local actors, which was facilitated by a Multiple Criteria Decision Analysis (MCDA). MCDA turned out to be instrumental for integrated planning approaches and transparent decision-making with broad public participation. Our results underline that endogenous development and new modes of governance are hampered by provisions of superior administrative bodies due to inadequate translation of the policy instrument's intervention logic. Reviewing European and national LEADER guidelines seems important for better using the endogenous regional potential and reaching higher positive impact on local governance structures.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; endogenous regional development; LEADER; multiple criteria decision analysis; Romania; governance